Characterization of graphene oxide functionalized carbon foam as a potential material for different applications - El-Yaqub, Balarabe; Wahid, Mohd Haniff; Zainal, Zulkarnain; Abdullah, Abdul Halim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Due to its cheap production, high electrical conductivity, simplicity of doping, and enhanced hydrophilic characteristic, porous carbon foam has a lot of potential for energy storage and conversion applications. In this study, graphene oxide (GO) was successfully grafted onto carbon foam using a simple dip coating technique with the help of a linker. 3D porous carbon foams were created using a one-step carbonization from commercial melamine foam. The material was characterized using XRD, FTIR, BET, TGA, XPS, Raman and FESEM to confirm its structural, functional group, surface area, thermal stability, and morphological characteristics. The stress-strain tests of the samples were conducted on an electronic universal testing machine. These foams have sufficient surface area (99 m2/g), a high level of C content (79.15%), and excellent compressibility. Moreover, as a proposed material for different applications, this distinctive GO grafted porous carbon foam also has the tendency to deliver remarkable performance in different fields of study. In conclusion, the GO grafted porous carbon foams have excellent prospects for different applications due to the straightforward preparation process and fascinating properties.